Effects of historical physics vignettes on student's understanding on the nature of science and epistemological beliefs toward learning physics - Del Carmen, Marc Vener C. (Animo Repository, 2018)
Despite this significance of science to every mans life, a considerable number of the population lacks understanding of scientific operations. Nature of science (NOS) teaching is viewed to complete the puzzle of scientific literacy and science learning. NOS refers to values and assumptions inherent to scientific knowledge and the development of scientific knowledge. Teaching nature of science to students develops awareness of the relevance of science in society which might help remove the disconnection of science to students as it stimulating their interests by showing science practicality. Historical Physics Vignettes were developed to serve as instructional material to teach NOS in senior high school. The material was validated by experts in terms of historical narratives, featured aspects of NOS, guide questions, language, overall presentation, illustrations, and additional activities through a researcher developed criterion based reference evaluation tool. Moreover, the HPV was used by two sections of Grade 12 STEM students of Congressional Integrated High School for their General Physics 2 subject. The pre-test and post-test results from EBAPS and VNOS-C revealed a significant difference on students VNOS before and after the general physics 2 course with intervention of HPV. On the other hand, no significant difference was found on students EBTLP before and after the course. There is a significant correlation between students VNOS and achievement in physics 2 course on 0.46 correlation coefficient. The regression analysis showed that around 20% of the construct of the participants grades can be accounted to the level of their VNOS. These findings may serve as a concrete evidence that teaching NOS to students will also lead to science content understanding.